Determination of Competition Conventional Bank in Banking Industry in Indonesia - Qori'ah, Ciplis Gema (UI Scholars Hub, 2016)
The aim of this study is to determine the level of concentration and competition behavior of conventional commercial banks in the national banking industry. This study focuses on descriptive analysis and quantitative analysis using panel data regression for 9 conventional commercial banks during 2003-2014. Results of eclectic analysis are supposed that behavior of banks is less competitive due to high levels of concentration in the banking industry. While the results of panel data regression show that the variables of bank interest expense, operating expense, other operating incomes and variable of loanable funds significantly affect the income of conventional banks.